Chinese Multinational Enterprises’ Internationalization Strategy in the new Globalisation era - Yin, Ge (2022)
Abstract Under the pattern of global economic integration, internationalization has become the main way to participate in global economic trade. Since China's joining the World Trade Organization (WTO), Chinese multinational enterprises are rapidly expanding in the international market and became the main force of foreign investment (FDI). However, Chinese enterprises are facing both opportunities and challenges when investing abroad. In developed markets, Chinese enterprises and some Chinese telecommunication equipment manufacturing enterprises are sanctioned, which greatly increases the difficulty of enterprise internationalization. The purpose of this research is to analyze the international development of China's multinational enterprises and take Huawei as the research object. This research analyzes the choice of Chinese enterprises' internationalization strategy from the aspects of the operating situation, internationalization motives, strengths and weaknesses of enterprises and challenges in internationalization. Through the case study of Huawei, the defects of Chinese enterprises in internationalization are identified, and the suggestions for the future development of Chinese multinational enterprises and the telecommunication equipment industry are put forward. The theory of this dissertation applies Dunning’s Motives for FDI, OLI theory, institutional theory, and combines the international strategic choice of Chinese multinational enterprises to analyze it. At last, some key factors influencing the internationalization development of Chinese communication equipment enterprises are summarized.